Letter to Mrs. Daniel Tolmach; Camarillo State Hospital From F.H Garrett - F.H. Garrett:::::: (1960)
Letter to Mrs. Daniel Tolmach and the Camarillo State Hospital from F.H Garrett (Superintendent and Medical Director) sent on May 24, 1960. The letter is an invitation to a two-day symposium on the understanding of a mentally ill offender and scientific research into causes and treatment of the illness, etc. This symposium will be led by the Department of Hygiene and the Atascadero State Hospital on June 20th & 21st, 1960.